Incidence of Malignancy on Tacrolimus Monotherapy Versus Combination Therapy: A Report from the TICTAC Trial - Baran, D.A.; Vefali, H.; Costa, V.; Guerrero-Miranda, C.Y.; Weiss, J.A.; Pieretti, J.; Gidea, C.G.; Camacho, M.; Zucker, M.J. (The Journal of heart and lung transplantation, 2013)
Recent ISHLT Registry reports indicate approximately 20 % of patients will suffer a malignancy within 5 years post-transplant. The propensity towards malignancy is directly associated with immunosuppression, which is typically a combination of a calcineurin inhibitor, cell cycle modifier and steroids. However, patients in the recently reported TICTAC trial were treated with tacrolimus (TAC) monotherapy or TAC / mycophenolate mofetil (MMF) along with universal steroid weaning within the first 8-10 weeks post-transplant. We examined the incidence of malignancy in subjects from the TICTAC trial to assess the risk of malignancy in patients according to immunosuppressive strategy. As previously described, from 4/04 – 8/08 150 adult heart transplant patients were enrolled and randomized to monotherapy or dual therapy with TAC and MMF. Patients were followed for survival and the occurrence of malignancies long-term. The table below shows the occurrence of malignancy post-transplant. The freedom from malignancy was similar between the monotherapy and TAC/MMF groups. Survival was similar between groups regardless of the incidence of cancer. TAC monotherapy is likely the minimum immunosuppression feasible in heart transplantation. There was no difference in the incidence of malignancy between groups. These results might reflect the inherent carcinogencity of TAC. MalignancyTAC Monotherapy Group (n=79)TAC / MMF Group (n=71)p-valuePre-transplant history of malignancy10.1 % (8 pts)4.2 % (3 pts)0.16Any Malignancy post-transplant30.4 % (20 pts)23.9 % (17 pts)0.38Hematologic malignancy post-txp3.8% (3 pts)7.0% (5 pts)0.38Skin malignancy post-txp17.7% (14 pts)14.1% (10 pts)0.54Freedom From Malignancy 1 Year Post Txp92.2%97.2%0.72Freedom From Malignancy 3 Years Post Txp85.2 %91.4%0.72Freedom From Malignancy 5 Years Post Txp76.7%79.8%0.72Survival 7 years Post-Txp: NO MALIGNANCY78.7 %91.1%0.56Survival 7 yrs Post-Txp: WITH MALIGNANCY86.1%75%0.56